Identification of Independent Predictors of Increased 90-Day Complication and Revision Rates Following Total Elbow Arthroplasty - Bryce F Kunkle BS; Nicholas A Baxter BS; Megan E Welsh BS; Richard J Friedman MD, FRCSC; Josef K Eichinger MD (Journal of Shoulder and Elbow Arthroplasty, 2023)
Introduction Total elbow arthroplasty (TEA) is an increasingly popular surgical option for many debilitating conditions of the elbow. There currently exists a paucity of literature regarding patient and hospital factors that lead to inferior outcomes following TEA. The purpose of this study is to identify independent predictors of increased complication and revision rates following TEA. Methods The National Readmissions Database (NRD) was queried from 2011 to 2018 to identify all cases of TEA (n = 8932). Relevant patient demographic factors, comorbidities, and hospital characteristics were identified and run in a univariate binomial logistic regression model. All significant variables were included in a multivariate binomial logistic regression model for data analysis. Results Independent predictors of increased complication rates included age, female sex, Medicare and Medicaid payer status, medium bed-sized center, and 18 of 34 medical comorbidities (all P  < .05). Independent predictors of increased revision rates included medium bed-sized centers, non-teaching hospital status, chronic pulmonary disease, depression, and pulmonary circulatory disorders (all P  < .05). Conclusion This study identified several patient and hospital characteristics that are independently associated with both increased complication and revision rates following TEA. This information can aid orthopedic surgeons during shared decision making when considering TEA in patients. Level of Evidence Level III, retrospective cohort study.